Antiviral Effects of Oleandrin - Newman RA; Sastry KJ; Arav-Boger R; Cai H; Matos R; Harrod R (Dove Medical Press, 2020)
Robert A Newman, 1, 2 K Jagannadha Sastry, 3 Ravit Arav-Boger, 4 Hongyi Cai, 5 Rick Matos, 6 Robert Harrod 7 1Department of Experimental Therapeutics, The University of Texas M. D. Anderson Cancer Center, Houston, TX 77054, USA; 2Phoenix Biotechnology, Inc, San Antonio, TX 78217, USA; 3Departments of Thoracic, Head and Neck Medical Oncology and Veterinary Sciences, The University of Texas MD Anderson Cancer Center, Houston, TX 77030, USA; 4Division of Infectious Diseases, Department of Pediatrics, Medical College of Wisconsin, Milwaukee, WI 53226, USA; 5National Institute of Diabetes and Digestive and Kidney Diseases, National Institutes of Health, Bethesda, MD 20892, USA; 6Innovar, LLC, Plano, TX 75025, USA; 7Department of Biological Sciences, the Dedman College Center for Drug Discovery, Design & Delivery, Southern Methodist University, Dallas, TX 75275, USACorrespondence: Robert A Newman Tel +1-7138578921Email newmanscientificconsulting@gmail.comAbstract: Over the past 15 years, investigators have reported on the utility and safety of cardiac glycosides for numerous health benefits including those as treatments for malignant disease, stroke-mediated ischemic injury and certain neurodegenerative diseases. In addition to those, there is a growing body of evidence for novel antiviral effects of selected cardiac glycoside molecules. One unique cardiac glycoside, oleandrin derived from Nerium oleander, has been reported to have antiviral activity specifically against ‘enveloped’ viruses including HIV and HTLV-1. Importantly, a recent publication has presented in vitro evidence for oleandrin’s ability to inhibit production of infectious virus particles when used for treatment prior to, as well as after infection by SARS-CoV-2/COVID-19. This review will highlight the known in vitro antiviral effects of oleandrin as well as present previously unpublished effects of this novel cardiac glycoside against Ebola virus, Cytomegalovirus, and Herpes simplex viruses.Keywords: oleandrin, Nerium oleander, virus, Na, K-ATPase, antiviral therapy